Nsd2 Represses Endogenous Retrovirus MERVL in Embryonic Stem Cells - Tingting Gao; Fuquan Chen; Wenying Zhang; Xuan Zhao; Xiao Hu; Xinyi Lu (Hindawi Limited, 2021)
The facilitates chromatin transcription (FACT) complex is a histone H2A/H2B chaperone, which represses endogenous retroviruses (ERVs) and transcription of ERV-chimeric transcripts. It binds to both transcription start site and gene body region. Here, we investigated the downstream targets of FACT complex to identify the potential regulators of MERVL, which is a key 2-cell marker gene. H3K36me2 profile was positively correlated with that of FACT component Ssrp1. Among H3K36me2 deposition enzymes, Nsd2 was downregulated after the loss of Ssrp1. Furthermore, we demonstrated that Nsd2 repressed the expression of ERVs without affecting the expression of pluripotency genes. The expression of MERVL and 2-cell genes was partially rescued by Nsd2 overexpression. The enrichment of H3K36me2 decreased on MERVL-chimeric gene in ESCs without Ssrp1. Our study discovers that Nsd2 is a repressor of MERVL, and FACT partially represses MERVL expression by regulating the expression of Nsd2 and its downstream H3K36me2.